A STUDY ON THE SOCIAL BACKGROUND OF WOMEN DRUG ADDICTS WITH SPECIAL REFERENCE TO THE MIRIHANA POLICE AREA - Dharmasiri, K.S.; De Silva, Banuka; Dissanayake, Pamudi (Universitas Hasanuddin, 2025)
Drug addiction is a global issue with severe consequences. Once predominantly linked to men, rising substance abuse among women, especially in Eastern societies like Sri Lanka, has become a concern. This study investigated socio-economic, cultural, and environmental factors influencing female substance abuse in the Mirihana Police area of Colombo District. Using semi-structured interviews with 50 women, the study identified that 42% of participants, aged 28–37, were most vulnerable. Most were Sinhalese (80%), Buddhist (52%), and of low education, with 48% having completed only five years of school. Major contributory causes were economic: husbands not being employed (57%), and financial need resulting in prostitution (12%). The main reasons for initiating drug use were friends (46%) and spouses (24%). The study highlights the need for gender-sensitive interventions, including community education, economic empowerment, and accessible rehabilitation services, to address systemic issues and reduce substance abuse among women in Sri Lanka.